Produktivitas dan Pola Musim Tangkap Ikan Peperek (Leiognathus spp.) di Teluk Banten - Yusfiandayani, Roza; Purbayanto, Ari; Nuraini, Ba’diah (Jurnal Ilmu Pertanian Indonesia, 2023)
Ponyfish (Leiognathus spp.) is one of the dominant types of fish landed at the Nusantara Fishing Port (PPN) Karangantu. Its high-intensity fishing activities are feared to cause future problems with the sustainability of ponyfish resources. This study aims to calculate fishing productivity, sustainable optimal fishing effort, maximum sustainable catch, and determine the pattern of fishing season in Banten Bay. The research was conducted from April to June 2021 at PPN Karangantu. The fishing gear analyzed were fixed lift nets, floating lift nets, and seine nets. Fishing productivity was calculated from catch per unit effort; the maximum sustainable catch was analyzed using the Schaefer, Fox, and Walter-Hilborn regression models. The seasonal pattern of the ponies was determined from the Fishing Season Index. The results showed that pony fishing productivity in PPN Karangantu decreased from 2016 to 2020. The optimum fishing effort value and the optimum catch through the Schaefer model were 2088 trips/year and 276.12 tons/year, respectively; the highest fishing season occurred in November (145.5%) and the lowest in May (70.2%). Based on the analysis of the Schaefer, Fox and Walter-Hilborn models, the exploitation of Ponyfish (Leiognathus spp.) in Banten Bay can be said to be over-exploited. Keywords: catching season, Banten bay, Leiognathus spp., productivity